Consumer-driven nutrient recycling of freshwater decapods: linking ecological theories and application in integrated multitrophic aquaculture - Musin, Gabriela Eliana (2023)
The Metabolic Theory of Ecology (MTE) and the Ecological Stoichiometry Theory (EST) arecentral and complementary in the consumer-driven recycling conceptual basis. The understandingof physiological processes of organisms is essential to explore and predict nutrientrecycling behavior, and to design integrated productive systems that efficiently use the nutrientinputs through an adjusted mass balance. We fed with fish-feed three species of decapods(prawn, anomuran, crab) from different families and with aquacultural potential toexplore the animal-mediated nutrient dynamic and its applicability in productive systems.We tested whether body mass, body elemental content, and feeds predict N and P excretionrates and ratios within taxa. We also verified if body content scales allometrically with bodymass within taxa. Finally, we compared the nutrient excretion rates and body elemental contentamong taxa. N excretion rates of prawns and anomurans were negatively related tobody mass, emphasizing the importance of MTE. Feed interacted with body mass to explainP excretion of anomurans and N excretion of crabs. Body C:N content positively scaled withbody mass in prawns and crabs. Among taxa, prawns mineralised more N and N:P, andless P, and exhibited higher N and C body content (and lower C:N) than the other decapods.Body P and N:P content were different among all species. Body content and body masswere the main factors that explained the differences among taxa and influence the role ofcrustaceans as nutrient recyclers. These features should be considered to select complementaryspecies that efficiently use feed resources. Prawns need more protein in feed andmight be integrated with fish of higher N-requirements, in contrast to crabs and anomurans.Our study contributed to the background of MTE and EST through empirical data obtainedfrom decapods and it provided insightful information to achieve more efficient aquacultureintegration systems.